Thermometry of combustion gases using light emission and acoustic wave from laser-induced sparks. (28th May 2019) - Lee, Jungwun; Bong, Cheolwoo; Sun, Hojoong; Jeong, Jinkyu; Bak, Moon Soo
Abstract: A new method to measure local combustion gas temperatures is proposed using light emission and acoustic wave from laser-induced sparks. Because the speed of sound is a function of temperature as well as species composition, the time-of-arrival measurements of the acoustic waves from each of the two laser-induced sparks separated by a certain distance were carried out using a high-frequency response microphone. As the microphone was installed in the same plane and line as the two laser sparks, the acoustic wave from the laser spark farther from the microphone traveled through the same region as the acoustic wave from the laser spark nearer to the microphone, and thus, the speed of sound for the region between the sparks can be estimated from the difference in the arrival times. Optical emission spectroscopy was also carried out on one of the laser sparks to estimate the species composition, and the linear relationship between the intensity ratio of atomic hydrogen to oxygen and fuel–air equivalence ratio was confirmed. Assuming that the gas reached its equilibrium state, the temperatures were obtained from the measured speed of sound and found to be systematically higher than the adiabatic flame temperatures by approximately 77 K. The repeatability of the measurement was within  ±38 K. The proposed method is appropriate for applications in which the temperature is high and contact measurements are difficult.